Linguistic and Cognitive Skills in Sardinian–Italian Bilingual Children - Garraffa, Maria; Beveridge, Madeleine; Sorace, Antonella (Frontiers in Psychology, 2015)
We report the results of a study which tested receptive Italian grammatical competence and general cognitive abilities in bilingual Italian–Sardinian children and age-matched monolingual Italian children attending the first and second year of primary school in the Nuoro province of Sardinia, where Sardinian is still widely spoken. The results show that across age groups the performance of Sardinian–Italian bilingual children is in most cases indistinguishable from that of monolingual Italian children, in terms of both Italian language skills and general cognitive abilities. However, where there are differences, these emerge gradually over time and are mostly in favor of bilingual children.